PERANAN KEPALA DESA TERHADAP PEMBERDAYAAN MASYARAKAT DI DESA BETAO RIASE KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Selviana Selviana (PRAJA: Jurnal Ilmiah Pemerintahan, 2017)
This study aims to determine, 1). the role of the village head in community empowerment, 2). the factors that influence the role of the village head on community empowerment in the village of Betao Riawa, Pitu Riawa District, Sidenreng Rappang Regency. The data collection methods in this study used observation techniques, literature studies, interviews and questionnaires. The collected data is then processed and analyzed using quantitative descriptive analysis techniques with frequency tables. The results obtained are the role of the village head in community empowerment in Betao Riase Village, Pitu Riawa District, Sidenreng Rappang Regency, especially the village head's role indicator is considered good (63.62%), community empowerment indicators are considered good (62%) and the factors that influence the role of the village head, especially the authority factor, was considered good (69.25%), the power factor was considered good (70%), and the population condition factor was considered quite good (79.5%).